Story of Medicine - Ward, Brian (Lorenz Books New York, 2000)
Healthy mind and body -- Earliest medicine -- Shamans and the supernatural -- Ayurvedic medicine -- Chinese medicine -- Hippocrates and the greeks -- Roman medicine -- Arab world -- Galen's legacy -- Renaissance discoveries -- Plague and pestilence -- Making diagnosis -- Rise of surgery -- Germ-free and pain-free -- Quacks and charlatans -- Public health -- Microbe hunters -- Immunization -- Germ killers -- Woman pioneers -- Rebuilding the body -- Healing the mind -- Plants and pills -- Alternative therapies -- Holistic medicine -- Modern technology -- Imaging the body -- Looking to the future.
Medicine around the world and across the ages.
10 - 13 years
Keywords: Medicine -- history -- juvenile